Dual Inhibition of mTORC1/2 Reduces Migration of Cholangiocarcinoma Cells by Regulation of Matrixmetalloproteinases - Joechle, Katharina; Jumaa, Huda; Thriene, Kerstin; Hellerbrand, Claus; Kulemann, Birte; Fichtner-Feigl, Stefan; Lang, Sven A.; Guenzle, Jessica (Frontiers in Cell and Developmental Biology, 2022)
Cholangiocarcinoma (CCA) is a rare but highly aggressive tumor entity for which systemic therapies only showed limited efficacy so far. As OSI-027 – a dual kinase inhibitor targeting both mTOR complexes, mTORC1 and mTORC2 - showed improved anti-cancer effects, we sought to evaluate its impact on the migratory and metastatic capacity of CCA cells in vitro. We found that treatment with OSI-027 leads to reduced cell mobility and migration as well as reduced surviving fraction in colony-forming ability. While neither cell viability nor proliferation rate was affected, OSI-027 decreased the expression of MMP2 and MMP9. Moreover, survival as well as anti-apoptotic signaling was impaired upon the use of OSI-027 as determined by AKT and MAPK blotting. Dual targeting of mTORC1/2 might therefore a viable option for anti-neoplastic therapy in CCA.